Self‐efficacy of ADRD caregivers: Results of a pilot survey: Dementia care research (research projects; nonpharmacological)/Family/Lay caregiving. (7th December 2020) - Parsons, Kelly Kazee; Gibson, Allison; Bardach, Shoshana H; Barber, Justin M; Johnson, Julia; Jicha, Gregory A
Abstract: Background: Family members often become informal caregivers of persons diagnosed with Alzheimer's disease and related dementias (ADRD). Caregiver self‐efficacy is a construct that refers to a belief that a person has about one's ability to successfully facilitate their caregiving role. However, self‐efficacy can vary across caregiving domains. This pilot study aimed to identify challenges and strengths of caregiver self‐efficacy to inform a caregiving intervention. Methods: Data collection was administered to ADRD caregivers associated with a southern U.S. Alzheimer's Disease Research Center. With a focus on motivation, coping, and self‐ efficacy, analysis was conducted with 65 caregivers for ADRD (n=62). The caregiver assessment was conducted as an interview (39 items) and included Zarit's Caregiver Burden 4‐item screening, REACH II Risk Appraisal, Fortinsky's Caregiver Self‐Efficacy for Managing Dementia scale, and selected items of Albert's Care Planning for Individuals with Dementia. Analysis in R identified caregiver efficacy along the continuum of care needs and domains. Results: Of the 62 respondents, 29 identified as the only caregiver (51.8%) and 51 identified as the primary caregiver (91.1%). The majority of respondents provided daily care (49; 87.5%) without paid assistance (43, 76.8%). Caregivers expressed challenges including frequent trouble sleeping (24; 42.9%) and occasional desire to yell at the persons with ADRD (28; 50.0%). Further, 27 persons with ADRD had access to a weapon (48.2%). Most caregivers "agreed a lot" (26; 44.6%) or "agreed a bit" (18; 32.1%) that providing care made them feel good about themselves. Self‐efficacy and caregiver burden were correlated. ([r(53) = ‐.413, p = .002]). Further, a regression was significant with independent variables level of disease knowledge and caregiver efficacy explaining significant variance in feeling good about providing care ([R2= .141, F(2, 52) = 4.114, p = 0.022]). Conclusion: Developing strategies to provide specific interventions within the continuum of care is a timely cost effective way to reduce caregiver burden, promote the dyad well‐being, and assist family to age in place. Caregiver interventions should focus on safety in the home (i.e., securing weapons), self‐care for caregivers, and disease education, which can empower caregivers to feel good about themselves in their role as caregivers.